DOMESTIC CAT (Felis catus) AS A TRANSMISSION LINK FOR DERMATOPHYTOSIS BY Microsporum canis TO HUMANS– CASE REPORT - LAURO CESAR FEITOSA; Caio Barbosa Brasileiro; Siluana Benvindo Ferreira; Bruno Leandro Maranhão Diniz; Diana Sousa Alcantara; Taciana Galba da Silva Tenório; Taciana Galba da Silva Tenório (Revista de Ciência Veterinária e Saúde Pública, 2020)
Microsporum canis, a species considered to be zoophilic, is referred to as the mains causative agente of dermatophytosis, being the one that has the highest occurrence in dogs and cats, as well as the main agente responsible for zoophilic dermatophytic infections in humans. The objective of this work was to report a case of familial microepidemic by M. canis in the city of Teresina, Piauí.